Improved Synthesis of Sulfur-Containing Glycosides by Suppressing Thioacetyl Migration - Luo, Tao; Zhang, Ying; Xi, Jiafeng; Lu, Yuchao; Dong, Hai (Frontiers in Chemistry, 2020)
Complex mixtures were often observed when we attempted to synthesize 4-thio- and 2,4-dithio-glycoside derivatives by double parallel and double serial inversion, thus leading to no or low yields of target products. The reason was later found to be that many unexpected side products were produced when a nucleophile substituted the leaving group on the substrate containing the thioacetate group. We hypothesized that thioacetyl migration is prone to occur due to the labile thioacetate group even under weak basic conditions caused by the nucleophile, leading to this result. Therefore, we managed to inhibit the generation of thiol groups from thioacetate groups by the addition of an appropriate amount of conjugate acid/anhydride, successfully improving the synthesis of 4-thio- and 2,4-dithio-glycoside derivatives. The target products which were previously difficult to synthesize, were herein obtained in relatively high yields. Finally, 4-deoxy- and 2,4-dideoxy-glycoside derivatives were efficiently synthesized through the removal of thioacetate groups under UV light, starting from 4-thio- and 2,4-dithio-glycoside derivatives.